Serway Physics for Science Engineers - Raymond A Serway (Cengage Learning, Inc, 2000)
Available in single hardcover volumes, 2-volume hardcover sets, and 4- or 5-volume softcover sets as listed below. This bestselling calculus-based introductory physics text for science and engineering students is recognized throughout the world for its clear and logical presentation of the basic concepts and principles of physics. The carefully crafted revision introduces coauthor Robert Beichner and contributing author John W. Jewett, Jr., who bring to the new edition their experience and talent in the area of physics education. The historically strong problem-solving approach has been further enhanced through increased realism in the worked examples and through additional guidance to students in building a systematic, step-by-step approach to solving homework problems. An updated ancillary package including full multimedia support, on-line homework plus a content-rich Web site for instructors and students complements this unsurpassed textbook and is more fully integrated with the text than ever before